2014
DOI: 10.1007/s00248-013-0361-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Link Between Imipenem Resistance and Biofilm Formation by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa, a ubiquitous environmental organism, is a difficult-to-treat opportunistic pathogen due to its broad-spectrum antibiotic resistance and its ability to form biofilms. In this study, we investigate the link between resistance to a clinically important antibiotic, imipenem, and biofilm formation. First, we observed that the laboratory strain P. aeruginosa PAO1 carrying a mutation in the oprD gene, which confers resistance to imipenem, showed a modest reduction in biofilm formation. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…This study found that out of 24 strains of P. aeruginosa studied, 16 were biofilm producers and most of the biofilm forming strains were resistant to gentamicin and ciprofloxacin. This strongly supports the earlier studies that there may be an unidentified mechanism between planktonic antibiotic resistance and biofilm formation because there is a need for higher concentration of antibiotics to kill biofilm cells than planktonic cells [15]. It was also noted in this study that antibiotics such as gentamicin and ciprofloxacin which are thought to be a first choice of antibiotics for Pseudomonas infections is not true anymore because both the planktonic and biofilm-forming cells showed extreme resistance to gentamicin and ciprofloxacin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study found that out of 24 strains of P. aeruginosa studied, 16 were biofilm producers and most of the biofilm forming strains were resistant to gentamicin and ciprofloxacin. This strongly supports the earlier studies that there may be an unidentified mechanism between planktonic antibiotic resistance and biofilm formation because there is a need for higher concentration of antibiotics to kill biofilm cells than planktonic cells [15]. It was also noted in this study that antibiotics such as gentamicin and ciprofloxacin which are thought to be a first choice of antibiotics for Pseudomonas infections is not true anymore because both the planktonic and biofilm-forming cells showed extreme resistance to gentamicin and ciprofloxacin.…”
Section: Discussionsupporting
confidence: 90%
“…The rate of biofilm-forming multi-drug resistant P. aeruginosa is increasing in India and the developing antibiotic-resistant biofilm forming P. aeruginosa is worrisome [14]. Recent studies showed that biofilm producing P. aeruginosa isolated from clinical samples were resistant to amikacin, imipenem, ciprofloxacin and gentamicin [14][15][16]. This study found that out of 24 strains of P. aeruginosa studied, 16 were biofilm producers and most of the biofilm forming strains were resistant to gentamicin and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of possible changes in membrane protein profiles, gene expression or production of reactive oxygen species could help to understand the observed differences in these strains. As a consequence, and as has been observed for other organisms (Musafer et al, 2014), in vitro analysis of K. pneumoniae biofilm formation capacity does not necessarily correlate with drug resistance -an aspect that merits more detailed studies using clinical isolates given the importance of this pathogen in HAI infections.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our findings showed that carbapenemase-producing isolates formed less biofilm than ESBL-producing and non-producing isolates. Recent studies demonstrate different results, carbapenemase producers P.aureginosa and A. baumannii formed stronger biofilms than carbapenemase negative isolates [33][34][35] and an inverse relationship between imipenem-meropenem resistance and biofilm formation [36,37]. These different results can be explained by the clonality (or hetrogeneity) of the carbapenemase-producing isolates [33].…”
Section: Discussionmentioning
confidence: 99%